Influence of Bradyrhizobium Inoculation and Fungicide Seed Treatment on Development and Yield of Cowpea, Lablab, and Soybean - Bulyaba, Rosemary; Lenssen, Andrew W. (Crop, Forage & Turfgrass Management, 2017)
Core Ideas Cowpea did not require Bradyrhizobium inoculation for nodulation. Lablab required Bradyrhizobium inoculation for nodulation. Fungicide seed treatment did not compromise nodulation of cowpea or lablab. Cowpea [Vigna unguiculata (L.) Walp.] and lablab (Lablab purpureus L.) are grain legumes with limited testing for grain, forage, and cover crop use in the US Corn Belt. We conducted a 2-year field study to determine the influence of Bradyrhizobium spp. inoculation and fungicide seed treatment on development, nodulation, and yield of selected grain legumes. Soybean [Glycine max (L.) Merr.] was included as a well-understood control. The experimental design was a randomized complete block in a factorial of four grain legumes with and without Bradyrhizobium spp. inoculation and a fungicide seed treatment. The cultivars used in the experiment were soybean P92Y82, cowpeas CA46 and Top Crop, and lablab Rongai. The seed treatments were fungicide, mefenoxam + fludioxonil (ApronMaxx), and Bradyrhizobium spp. inoculant. The two experimental sites had four blocks each year, every block consisting of 16 plots with different crop–fungicide–Bradyrhizobium combinations. Each crop had four treatments: fungicide only, Bradyrhizobium spp. inoculant only, fungicide + inoculant, and a control (with no fungicide or inoculant). Cowpea plants had numerous functional nodules (pinkish or reddish on the inside) in the absence of Bradyrhizobium spp. inoculation, but lablab never produced any nodules without inoculation. We found no significant effects of Bradyrhizobium spp. inoculation and fungicide seed treatment on cowpea, lablab, or soybean grain yield.